6.73 Problems 7201 to 7300

Table 6.145: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

7201

\[ {}\left (x^{2}-25\right ) y^{\prime \prime }+2 x y^{\prime }+y = 0 \]

7202

\[ {}\left (x^{2}-25\right ) y^{\prime \prime }+2 x y^{\prime }+y = 0 \]

7203

\[ {}\left (x^{2}-2 x +10\right ) y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

7204

\[ {}\left (x^{2}-2 x +10\right ) y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

7205

\[ {}y^{\prime \prime }-x y = 0 \]

7206

\[ {}y^{\prime \prime }+x^{2} y = 0 \]

7207

\[ {}y^{\prime \prime }-2 x y^{\prime }+y = 0 \]

7208

\[ {}y^{\prime \prime }-x y^{\prime }+2 y = 0 \]

7209

\[ {}y^{\prime \prime }+x^{2} y^{\prime }+x y = 0 \]

7210

\[ {}y^{\prime \prime }+2 x y^{\prime }+2 y = 0 \]

7211

\[ {}\left (x -1\right ) y^{\prime \prime }+y^{\prime } = 0 \]

7212

\[ {}\left (x +2\right ) y^{\prime \prime }+x y^{\prime }-y = 0 \]

7213

\[ {}y^{\prime \prime }-\left (1+x \right ) y^{\prime }-y = 0 \]

7214

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-6 y = 0 \]

7215

\[ {}\left (x^{2}+2\right ) y^{\prime \prime }+3 x y^{\prime }-y = 0 \]

7216

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+x y^{\prime }-y = 0 \]

7217

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

7218

\[ {}\left (1+x \right ) y^{\prime \prime }-\left (2-x \right ) y^{\prime }+y = 0 \]

7219

\[ {}y^{\prime \prime }-2 x y^{\prime }+8 y = 0 \]

7220

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime } = 0 \]

7221

\[ {}y^{\prime \prime }+y \sin \left (x \right ) = 0 \]

7222

\[ {}y^{\prime \prime }+{\mathrm e}^{x} y^{\prime }-y = 0 \]

7223

\[ {}y^{\prime \prime }+x y^{\prime }+y = 0 \]

7224

\[ {}x^{3} y^{\prime \prime }+4 x^{2} y^{\prime }+3 y = 0 \]

7225

\[ {}x \left (x +3\right )^{2} y^{\prime \prime }-y = 0 \]

7226

\[ {}\left (x^{2}-9\right )^{2} y^{\prime \prime }+\left (x +3\right ) y^{\prime }+2 y = 0 \]

7227

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}+\frac {y}{\left (x -1\right )^{3}} = 0 \]

7228

\[ {}\left (x^{3}+4 x \right ) y^{\prime \prime }-2 x y^{\prime }+6 y = 0 \]

7229

\[ {}x^{2} \left (x -5\right )^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}-25\right ) y = 0 \]

7230

\[ {}\left (x^{2}+x -6\right ) y^{\prime \prime }+\left (x +3\right ) y^{\prime }+\left (x -2\right ) y = 0 \]

7231

\[ {}x \left (x^{2}+1\right )^{2} y^{\prime \prime }+y = 0 \]

7232

\[ {}x^{3} \left (x^{2}-25\right ) \left (x -2\right )^{2} y^{\prime \prime }+3 x \left (x -2\right ) y^{\prime }+7 \left (x +5\right ) y = 0 \]

7233

\[ {}\left (x^{3}-2 x^{2}+3 x \right )^{2} y^{\prime \prime }+x \left (x -3\right )^{2} y^{\prime }-\left (1+x \right ) y = 0 \]

7234

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+5 \left (1+x \right ) y^{\prime }+\left (x^{2}-x \right ) y = 0 \]

7235

\[ {}x y^{\prime \prime }+\left (x +3\right ) y^{\prime }+7 x^{2} y = 0 \]

7236

\[ {}x^{2} y^{\prime \prime }+\left (\frac {5}{3} x +x^{2}\right ) y^{\prime }-\frac {y}{3} = 0 \]

7237

\[ {}x y^{\prime \prime }+y^{\prime }+10 y = 0 \]

7238

\[ {}2 x y^{\prime \prime }-y^{\prime }+2 y = 0 \]

7239

\[ {}2 x y^{\prime \prime }+5 y^{\prime }+x y = 0 \]

7240

\[ {}4 x y^{\prime \prime }+\frac {y^{\prime }}{2}+y = 0 \]

7241

\[ {}2 x^{2} y^{\prime \prime }-x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

7242

\[ {}3 x y^{\prime \prime }+\left (2-x \right ) y^{\prime }-y = 0 \]

7243

\[ {}x^{2} y^{\prime \prime }-\left (x -\frac {2}{9}\right ) y = 0 \]

7244

\[ {}2 x y^{\prime \prime }-\left (2 x +3\right ) y^{\prime }+y = 0 \]

7245

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {4}{9}\right ) y = 0 \]

7246

\[ {}9 x^{2} y^{\prime \prime }+9 x^{2} y^{\prime }+2 y = 0 \]

7247

\[ {}2 x^{2} y^{\prime \prime }+3 x y^{\prime }+\left (2 x -1\right ) y = 0 \]

7248

\[ {}x y^{\prime \prime }+2 y^{\prime }-x y = 0 \]

7249

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

7250

\[ {}x y^{\prime \prime }-x y^{\prime }+y = 0 \]

7251

\[ {}y^{\prime \prime }+\frac {3 y^{\prime }}{x}-2 y = 0 \]

7252

\[ {}x y^{\prime \prime }+\left (1-x \right ) y^{\prime }-y = 0 \]

7253

\[ {}x y^{\prime \prime }+y^{\prime }+y = 0 \]

7254

\[ {}x y^{\prime \prime }+\left (x -6\right ) y^{\prime }-3 y = 0 \]

7255

\[ {}x \left (x -1\right ) y^{\prime \prime }+3 y^{\prime }-2 y = 0 \]

7256

\[ {}x^{4} y^{\prime \prime }+\lambda y = 0 \]

7257

\[ {}x^{3} y^{\prime \prime }+y = 0 \]

7258

\[ {}x^{2} y^{\prime \prime }+\left (3 x -1\right ) y^{\prime }+y = 0 \]

7259

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{9}\right ) y = 0 \]

7260

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-1\right ) y = 0 \]

7261

\[ {}4 x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}-25\right ) y = 0 \]

7262

\[ {}16 x^{2} y^{\prime \prime }+16 x y^{\prime }+\left (16 x^{2}-1\right ) y = 0 \]

7263

\[ {}x y^{\prime \prime }+y^{\prime }+x y = 0 \]

7264

\[ {}y^{\prime }+x y^{\prime \prime }+\left (x -\frac {4}{x}\right ) y = 0 \]

7265

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (9 x^{2}-4\right ) y = 0 \]

7266

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (36 x^{2}-\frac {1}{4}\right ) y = 0 \]

7267

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (25 x^{2}-\frac {4}{9}\right ) y = 0 \]

7268

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (2 x^{2}-64\right ) y = 0 \]

7269

\[ {}x y^{\prime \prime }+2 y^{\prime }+4 y = 0 \]

7270

\[ {}x y^{\prime \prime }+3 y^{\prime }+x y = 0 \]

7271

\[ {}x y^{\prime \prime }-y^{\prime }+x y = 0 \]

7272

\[ {}x y^{\prime \prime }-5 y^{\prime }+x y = 0 \]

7273

\[ {}x^{2} y^{\prime \prime }+\left (x^{2}-2\right ) y = 0 \]

7274

\[ {}4 x^{2} y^{\prime \prime }+\left (16 x^{2}+1\right ) y = 0 \]

7275

\[ {}x y^{\prime \prime }+3 y^{\prime }+x^{3} y = 0 \]

7276

\[ {}9 x^{2} y^{\prime \prime }+9 x y^{\prime }+\left (x^{6}-36\right ) y = 0 \]

7277

\[ {}y^{\prime \prime }-x^{2} y = 0 \]

7278

\[ {}x y^{\prime \prime }+y^{\prime }-7 x^{3} y = 0 \]

7279

\[ {}y^{\prime \prime }+y = 0 \]

7280

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

7281

\[ {}16 x^{2} y^{\prime \prime }+32 x y^{\prime }+\left (x^{4}-12\right ) y = 0 \]

7282

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (16 x^{4}+3\right ) y = 0 \]

7283

\[ {}2 x y^{\prime \prime }+y^{\prime }+y = 0 \]

7284

\[ {}y^{\prime \prime }-x y^{\prime }-y = 0 \]

7285

\[ {}\left (x -1\right ) y^{\prime \prime }+3 y = 0 \]

7286

\[ {}y^{\prime \prime }-x^{2} y^{\prime }+x y = 0 \]

7287

\[ {}x y^{\prime \prime }-\left (x +2\right ) y^{\prime }+2 y = 0 \]

7288

\[ {}\cos \left (x \right ) y^{\prime \prime }+y = 0 \]

7289

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

7290

\[ {}\left (x +2\right ) y^{\prime \prime }+3 y = 0 \]

7291

\[ {}\left (1+x \right ) y^{\prime } = y \]

7292

\[ {}y^{\prime } = -2 x y \]

7293

\[ {}x y^{\prime }-3 y = k \]

7294

\[ {}y^{\prime \prime }+y = 0 \]

7295

\[ {}y^{\prime \prime }-y^{\prime }+x y = 0 \]

7296

\[ {}y^{\prime \prime }-y^{\prime }+x^{2} y = 0 \]

7297

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

7298

\[ {}y^{\prime \prime }+\left (x^{2}+1\right ) y = 0 \]

7299

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-2\right ) y = 0 \]

7300

\[ {}y^{\prime }+4 y = 1 \]